Treatment of pathological fractures due to brown tumours in a patient with hyperparathyroidism and lack of parafibromin expression – A case report. (December 2020) - Wasiak, Michał; Popow, Michał; Bogdańska, Magdalena; Starzyńska-Kubicka, Aleksandra; Małdyk, Paweł; Wasilewski, Piotr
Abstract: Brown tumours, known also as osteitis fibrosa cystica, are benign osteolytic lesions found in 5–15% of patients with hyperparathyroidism, and commonly located in mandibles, the shafts of long bones, the pelvis or ribs. As they compromise bone strength, pathological fractures can be a typical effect of their presence; but given the complex nature of the disease process in this case, such fractures require an interdisciplinary approach directed at orthopaedic treatment, plus management of the underlying hyperparathyroidism. In this paper, we present the case of a 36-year-old female patient with bilateral anophthalmia, hyperparathyroidism and nephrolithiasis, in whom a fall led to her sustaining a pathological fracture of the proximal third of the femoral shaft in the place of an osteolytic lesion, as well as second pathological fracture of the left patella also changed by multiple examples of such lesions. Parathyroidectomy on account of adenoma had been performed 2 weeks prior to the trauma. The femoral shaft fracture was treated surgically, the patella fracture conservatively, and a sample brown tumour was found in tissue. As the parathyroid showed no parafibromin expression, a diagnosis of HPT-JT (hyperparathyroidism and jaw tumour) was arrived at, with this condition given as caused by CDC73 mutation. This disease is able to account for brown tumours, hyperparathyroidism, benign or malignant tumours of kidneys, intestinal tract, and lungs. The approach combining treatment of the fractures with intervention over the parathyroid adenoma proved a successful one, with complete bone union ensuing, and no relapse into hyperparathyroidism 2 years on from the surgery. This case indicates the importance of an interdisciplinary approach to the treatment of brown tumours, as well as the necessity for a diagnosis to be extended when incidental brown tumours are found.